Ragam Doa Nabi Ibrahim dalam Al-Qur’an - Muhammad Soleh Ritonga (Tarbiyah : Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
Prayer occupies a central and indispensable role in Islam, particularly within the doctrinal framework of Ahl al-Sunnah wa al-Jama‘ah. It is considered an essential aspect of religious life that cannot be neglected. This is emphasized in the Qur’an, which affirms that the prophets consistently engaged in supplication to Allah, among them, Prophet Ibrahim is a prominent example. The Qur’an records numerous prayers, many of which are attributed to Prophet Ibrahim. His supplications encompass a broad range of intentions, including prayers for the well-being of the land, for himself, his descendants, his parents, and for the community of believers. Notably, the Qur’an records that a significant portion of his prayers were directed toward the welfare and guidance of his progeny. This indicates that supplication in Islam is not solely a personal act, but also a means of seeking divine mercy and blessings for others who share the faith.